Pengaruh Media Pembelajaran Powerpoint terhadap Hasil Belajar Siswa pada Mata Pelajaran TIK - Nika Monika; Muhammad Verendsyah; Yeremias Perikaes; Irut Apriyanti; Paulus Alesandro (Journal on Education, 2023)
This research is a quantitative research using The Nonequivalent Posttest Control Group Design method. The subjects of this study were students of class VIII MTS N 1 Pontianak. The samples used were students of class VIIIB as the experimental class and class IIC as the control class. The number of students in the experimental class is 30 students and the control class is 25 students. This study aims to see whether PowerPoint learning media has an influence on student learning outcomes. Data analysis was carried out to provide an overview of the data that has been collected from the research results. It is intended to find conclusions and test hypotheses. The data obtained from the results of the post test. Based on the research results, the average value of the experimental class was 78.3 with a standard deviation of 10.47. And the control class got an average score of 54.72 with a standard deviation of 10.31. From the results of the analysis it was found that tcount = 20.82 and ttable = 2.01 so that tcount > ttable. from these results it was concluded that powerpoint learning media had an influence on student learning outcomes in ICT subjects.